Gerakan Transformasi Pemuda Muslim pada Komunitas Berani Hijrah di Desa Tanjung Morawa A, Kecamatan Tanjung Morawa, Kabupaten Deli Serdang - Siregar, M. Parlin Ramadhana; Maraimbang, Maraimbang; Andy, Safria (Lembaga Yasin AlSys, 2025)
The rising phenomenon of the hijrah movement among Muslim youth is a response to the challenges posed by modern culture, which tends to be secular and permissive. This study aims to analyze the implementation of the Living Qur’an concept in shaping Islamic behavior and lifestyle among members of the Berani Hijrah Community in Tanjung Morawa A Village, Deli Serdang Regency. A qualitative approach was employed, using field research methods and the Living Qur’an framework to understand how Qur’anic teachings are internalized in daily life. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that the internalization of Qur’anic values occurs through regular study sessions, mentoring, communal tadarus, social activities, and digital dakwah. Challenges faced by the community include fluctuating member enthusiasm, limited funding, and negative influences from the environment and social media. Nevertheless, the exemplary leadership of community organizers and support from local figures play a crucial role in sustaining the movement. The study demonstrates that the Berani Hijrah Community effectively fosters youth who are more religious, respectful, mature in thought, and committed to a modest and positive lifestyle. This research contributes to strengthening youth transformation movements grounded in Qur’anic values in the modern era.